Transcriptional Organization of the Erythromycin Biosynthetic Gene Cluster of Saccharopolyspora erythraea - Reeves, Andrew R. (American Society for Microbiology, 1999)
The transcriptional organization of the erythromycin biosynthetic gene (ery) cluster of Saccharopolyspora erythraea has been examined by a variety of methods, including S1 nuclease protection assays, Northern blotting, Western blotting, and bioconversion analysis of erythromycin intermediates. The analysis was facilitated by the construction of novel mutants containing a S. erythraea transcriptional terminator within the eryAI, eryAIII, eryBIII, eryBIV, eryBV, eryBVI, eryCIV, and eryCVI genes and additionally by an eryAI −10 promoter mutant. All mutant strains demonstrated polar effects on the transcription of downstream ery biosynthetic genes. Our results demonstrate that the ery gene cluster contains four major polycistronic transcriptional units, the largest one extending approximately 35 kb from eryAI to eryG. Two overlapping polycistronic transcripts extending from eryBIV to eryBVII were identified. In addition, seven ery cluster promoter transcription start sites, one each beginning at eryAI, eryBI, eryBIII, eryBVI, and eryK and two beginning at eryBIV, were determined.